Case reportStent entrapment and guide wire fracture during percutaneous coronary intervention in the same patient - Tamci, Batuhan; Okan, Taha; Gungor, Hasan; Ozturk, Volkan; Cam, Fatih (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
In the performance of increasingly complex PCI there remains an ever-present risk of stent entrapment and guide wire or other device fracture. We report the first case with stent dislodgement and guide wire fracture to occur simultaneously in the same patient.